Cultural Mediation in Retirement Financial Planning: Examining Contextual Determinants of Outcomes - Yadav, Kalpana; Giri, Rita (DAV Research Journal, 2025)
The study seeks to uncover the extent to which clear retirement goals can motivate proactive financial engagement. This study aims to explore the mediating role of culture in shaping the retirement financial planning outcomes, providing a nuanced understanding of how individuals navigate their financial futures. The research employed explanatory research approach to determine the cause and effect relationship between variables. The data were collected by using structured questionnaires from 332 employees who were above 20 years of age. The study applied convenience sampling technique to collect the data. Descriptive statistics, Pearson correlation and regression analysis have been used to analyze the data and validate the generated hypothesis. The mediating analysis were analyzed by using Hayes’ PROCESS Macro (Model 4). The analysis from the study demonstrated that there was significantly positive relationship of Retirement Goal Clarity and Financial Risk Tolerance with Financial Planning for Retirement. Additionally, the result indicated that there was no significant relation of Financial Self Efficacy with Financial Planning for Retirement. The research discovered that culture is partially mediating in this relationship, indicating that culture directly and indirectly improves the financial planning for Retirement. The research aimed to investigate the mediating effect of culture on Financial Planning for Retirement. This paper contributed in an area where there is limited study done, exploring how the culture mediates in Financial Planning for retirement, Retirement Goal Clarity, Financial Risk Tolerance and Financial Self-Efficacy.